THE ROLE OF FISIOTERAPY IN PROMOTING HEALTH THROUGH UNIVERSITY EXTENSION (Fiep Bulletin - online, 2013)
The university extension is seen as one of the basic functions of the University. In the project of extension of the University "Attention to the health of children, adolescents and their caregivers" elected the promote the health as the main orientation. This study aimed to identify key postural disorders in children 5 to 15 years and promote educational posture. The documentary analysis method was used to develop this search. A obtain clinical data was based on individual assessment posture with objective to determine the prevalence of postural changes in students through the criteria proposed by Kendall, MC. From March to September 2008 to evaluate physical therapy and guided 78 students with the average age of 5 to 15 years. These were 38 male and 40 female. The main shortcomings were found in students: 19 (24%) inclination of the head to the right, 28 (35%) right shoulder higher, 38 (48%) knee valgus, 11 (14%) flat feet, 61 (78% ) Internal rotation of shoulder, 46 (58%) shoulder blades away from the costal grid, 24 (30%) dorsal kyphosis, 15 (19%) concavity of the thoracic spine to the left, 8 students (10%) hyperlordosis lumbar, 39 ( 50%) shoulders forward, 27 (34%) anterior head, 17 (21%) cervical spine forward, 34 (43%) abdominal protusos, 28 (35%) and lumbar hyperlordosis 8 (10%) students with hyperextension of the knee. These results are cause for concern because they are children, where the skeleton is now being formed and are more susceptible to deformations. Moreover, this is an age conducive to the establishment of healthy habits. This reinforces the idea that the school is responsible for the area of health promotion formalizing of the teaching-learning process, when the child is in the phase of growth.
Keywords: Physiotherapy; University extension; promotion of health